1995
DOI: 10.1042/bj3060147
|View full text |Cite
|
Sign up to set email alerts
|

Rapid purification and identification of calcyphosine, a Ca2+-binding protein phosphorylated by protein kinase A

Abstract: A method is presented for the rapid purification of dog thyroid calcyphosine, a protein previously identified as a major substrate for cyclic AMP-dependent protein kinase in dog thyroid slices stimulated by thyrotropin [Lecocq, Lamy and Dumont (1979) Eur. J. Biochem. 102, 147-152]. The protein was previously identified as a spot on two-dimensional gels and is now purified in its native form by a procedure involving three chromatographic steps. Homogeneous calcyphosine identified by SDS/PAGE, immunoblotting and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 9 publications
1
15
0
Order By: Relevance
“…The gene encodes a protein with a predicted calcium-binding domain and an EF Hand domain, and its closest human ortholog is a calcyphosine-like protein called CAPSL (Strausberg et al, 2002). Little is known about the functional role of vertebrate CAPSL protein, although calcyphosine is expressed in vertebrate thyroid and brain tissues (Halleux et al, 1998; Lecocq et al, 1995; Mailleux et al, 1993; Sauter et al, 1995). Loss of function alleles of this gene were not available at the time of our study, but we found that disruption of CG10126 via either of two different RNAi lines resulted in significant delays in border cell migration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The gene encodes a protein with a predicted calcium-binding domain and an EF Hand domain, and its closest human ortholog is a calcyphosine-like protein called CAPSL (Strausberg et al, 2002). Little is known about the functional role of vertebrate CAPSL protein, although calcyphosine is expressed in vertebrate thyroid and brain tissues (Halleux et al, 1998; Lecocq et al, 1995; Mailleux et al, 1993; Sauter et al, 1995). Loss of function alleles of this gene were not available at the time of our study, but we found that disruption of CG10126 via either of two different RNAi lines resulted in significant delays in border cell migration (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…23 As it is phosphorylated in a cAMP-dependent manner, it is considered to be implicated in the cross-signaling between these cascades to coordinate cellular proliferation and differentiation. 24 Some antiallergic drugs were observed to bind to CAPS with high affinity in bovine lung, which was considered to be in accord with its antiallergic property.…”
Section: Discussionmentioning
confidence: 99%
“…10 It is rapidly phosphorylated during full functional activation of the cell via the cAMP cascade but is not phosphorylated in response to acetylcholine, which activates the Ca 2+ phosphatidylinostol cascade. As it is phosphorylated in a cAMPdependent manner, it is considered to be implicated in the cross-signaling between these cascades to coordinate cellular proliferation and differentiation.…”
Section: Discussionmentioning
confidence: 99%